EKSPLORASI DESAIN MOTIF BATIK CIUNG WANARA DENGAN MULTITEKNIK PADA KEBAYA MODIFIKASI - Purwandaru, Kresna (Studi Budaya Nusantara, 2023)
Ciung Wanara is one of the cultural tourism objects in Ciamis Regency has various historical relics and is one of the prehistoric relics owned by Ciamis. Batik is one of the handicrafts in the form of textiles. Along with the development of the fashion world until now, it has led designers to be more innovative and creative in designing designs on batik and the techniques used. Initially, batik only used one technique, it was written and stamped. However, this time the writer wants to give a new nuance in a batik design. And in general, kebaya is made of brocade or other materials, with very simple fashion pieces. But this time the writer wants to give a modern touch to the kebaya dress with the intention of being another attraction and also expanding the existence of kebaya and batik in society as well as reviving local culture. This research is a descriptive qualitative research. At the data collection stage, the researcher used the observation method and the document method, namely by collecting the information needed, while the document technique was by collecting information in the form of data from books, journals, the internet and other sources. The data analysis technique used intraesthetic data analysis and extra-aesthetic data analysis. The creation process includes designing, executing, and finishing. After making several exploratory designs, 5 main designs were chosen which were used as contemporary motifs that were applied to the kebaya and top shawl based on the author's ideas and concepts. Through the creation of this work, it is hoped that it can provide the latest innovations in kebaya and batik clothing.